The Effects of Protein Supplement Intake in Adolescents - Impact on Health and Development - Sim, Aleksandra; Mioduszewska, Joanna; Rot, Paweł; Poniewozik, Piotr; Dziuba, Natalia; Pernal, Maja; Roguska, Zofia; Zuzak, Andrzej Paweł; Poniewozik, Paweł; Grabowski, Krzysztof (Quality in Sport, 2026)
Background: Over the past two decades, adolescent protein supplement consumption has surged, driven by social media "fitness culture" and evolving standards of muscularity. Despite protein’s role in pubertal development, there is a significant shift toward prioritizing processed supplements over whole-food sources, particularly among young males and athletes lacking professional oversight. Aim: This study synthesizes clinical evidence and position statements to evaluate the prevalence, efficacy, and safety of protein supplementation in adolescents, focusing on physiological risks and the correlation with disordered eating or muscle dysmorphia. Material and methods: The study reviews data from major health organizations regarding protein requirements for active versus sedentary youth and the efficacy of whey protein compared to whole foods. Results: Clinical evidence shows that while whey protein may marginally improve aerobic capacity, it does not enhance muscle mass or anaerobic power more effectively than whole-food protein. Significant concerns include supplement contamination, heavy metals, renal stress, and acne exacerbation via IGF-1 stimulation. A "gateway effect" also correlates excessive intake with disordered eating and body dysmorphia. Conclusions: Health organizations emphasize a "food-first" approach, recommending supplements only when dietary intake is insufficient. Educational interventions are vital to mitigate the risks of unsupervised supplement use in youth. Key words: protein supplements, adolescent health, sports nutrition, whey protein, body dysmorphia.